Composition of Vaginal Microbiota in Pregnant Women With Aerobic Vaginitis - Oh, Kwan Young; Lee, Sunghee; Lee, Myung-Shin; Lee, Myung-Ju; Shim, Eunjung; Hwang, Yun Ha; Ha, Joong Gyu; Yang, Yun Seok; Hwang, In Taek; Park, Jun Sook (Frontiers in Cellular and Infection Microbiology, 2021)
Vaginal dysbiosis, such as bacterial vaginosis (BV) and aerobic vaginitis (AV), is an important cause of premature birth in pregnant women. However, there is very little research on vaginal microbial distribution in AV compared to that in BV. This study aimed to analyze the composition of the vaginal microbiota of pregnant women with AV using microbial community analysis and identify the causative organism using each criterion of the AV scoring system. Also, we compared the quantification of aerobic bacteria using quantitative polymerase chain reaction (qPCR) and their relative abundances (RA) using metagenomics. This prospective case–control study included 228 pregnant Korean women from our previous study. A wet mount test was conducted on 159 women to diagnose AV using the AV scoring system. Vaginal samples were analyzed using metagenomics, Gram staining for Nugent score determination, conventional culture, and qPCR for Staphylococcus species, Streptococcus spp., and Enterobacteriaceae. The relative abundances (RAs) of eleven species showed significant differences among the three groups (Normal flora (NF), mild AV, and moderate AV). Three species including Lactobacillus crispatus, were significantly lower in the AV groups than in the NF group, while eight species were higher in the AV groups, particularly moderate AV. The decrease in the RA of L. crispatus was common in three criteria of the AV scoring system (Lactobacillary, WBC, and background flora grades), while it did not show a significant difference among the three grade groups of the toxic leukocyte criterion. Also, the RAs of anaerobes, such as Gardnerella and Megaspehera, were higher in the AV groups, particularly moderate AV, while the RAs of aerobes were very low (RA < 0.01). Therefore, qPCR was performed for aerobes (Staphylococcus spp., Streptococcus spp., and Enterobacteriaceae); however, their quantification did not show a higher level in the AV groups when compared to that in the NF group. Therefore, AV might be affected by the RA of Lactobacillus spp. and the main anaerobes, such as Gardnerella spp. Activation of leukocytes under specific conditions might convert them to toxic leukocytes, despite high levels of L. crispatus. Thus, the pathogenesis of AV can be evaluated under such conditions.